NARASI ZIONISME DALAM KLAIM ATAS YERUSALEM PADA MASA PEMERINTAHAN BENJAMIN NETANYAHU - Yudi Prawira (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2019)
Zionist narrative constitutes Netanyahu’s policy in Jerusalem. The use of narrative in conflict is important to build worldview either internally or externally to justify their ideological goal. This paper uses Constructivism framework to understand how Netanyahu’s worldview created by that narrative and replicates his worldview by using speech act. This paper uses qualitative interpretive method which focused on how to understand narrative. The objective of this research is to undertand Netanyahu’s position about Jerusalem according to Zionist ideology. I conclude that this conflict will remain as long as Netanyahu in power. It is hard to imagine about the possibility to reach the final agreement about two state solution especially in the most important issue like Jerusalem because the ideology that Netanyahu holds will not allow compromise.